A cross-sectional study to assess COVID-19 vaccine hesitancy among health care providers in a tertiary care centre, Tamil Nadu - Rajesh, Eshwar; Mathivanan, Sankarmani R.; Subramaniam, Sudarshini (International Journal Of Community Medicine And Public Health, 2022)
Background: The only way to reduce a person’s likelihood of contracting COVID-19 infection, hospitalization, and death from it is to get vaccinated. Healthcare providers are indefinitely exposed to the virus and are also a source of knowledge about the sickness and vaccination. However hesitancy towards vaccination among healthcare providers persists. To estimate the prevalence of COVID-19 vaccine hesitancy among healthcare providers and to assess its predictors. Methods: This cross-sectional study was conducted using an interviewer administered pretested semi-structured questionnaire adapting 5C vaccine acceptance/hesitancy questionnaire among 310 healthcare providers like doctors, nurses, multipurpose workers, support and paramedical staffs and students in a Tertiary care centre in Tamil Nadu selected by multistage random sampling from March to April of 2021. The collected data was analyzed by using Statistical package for social sciences (SPSS) version 16. Results: The results showed that overall, 29.35% (n=91) of healthcare providers had hesitancy towards vaccination. 48.7% of the total respondents were not vaccinated against COVID-19 (n=151) and 24.5% of them were unwilling to be vaccinated. The mean of 5C questionnaire score was taken as cut off and the psychological antecedents of COVID-19 vaccination were compared between those vaccinated and not vaccinated. Among those vaccinated, it was observed that they had high confidence in vaccination, collective responsibility and calculation. Conclusions: To battle misinformation and poor vaccination rates in future COVID-19 vaccination program, interventional educational efforts focusing on mitigating the constraints and complacence is urgently needed.